Photocatalytic, Fenton and photo-Fenton degradation of RhB over Z-scheme g-C3N4/LaFeO3 heterojunction photocatalysts. (1st August 2018) - Ye, Yongchun; Yang, Hua; Wang, Xiangxian; Feng, Wangjun
Abstract: Z-scheme g-C3 N4 /LaFeO3 heterojunction photocatalysts were prepared by calcining the uniformly mixed g-C3 N4 nanosheets and LaFeO3 nanoparticles at 300 °C for 1 h. The as-prepared g-C3 N4 /LaFeO3 composites were systematically characterized by XRD, SEM, TEM, XPS, UV–vis DRS, PL spectroscopy, EIS and photocurrent response. It is demonstrated that LaFeO3 nanoparticles (average size: ca. 35 nm) are uniformly assembled onto the surface of g-C3 N4 nanosheets through chemical bonding, leading to the formation of g-C3 N4 /LaFeO3 heterojunctions. The photocatalytic, Fenton and photo-Fenton performances of the samples were investigated by degrading RhB using simulated sunlight as the light source. Compared to bare LaFeO3 and g-C3 N4, the g-C3 N4 /LaFeO3 composites exhibit significantly enhanced photocatalytic and photo-Fenton degradation of the dye, and the maximum activity is observed for the 15%g-C3 N4 /LaFeO3 composite. Moreover, the photo-Fenton performance of the composites is much higher than the photocatalytic or Fenton performances. The much improved photo-fenton activity is ascribed to the efficient separation of photogenerated electron-hole pairs due to the Z-scheme electron transfer and the synergistic effect between LaFeO3 and g-C3 N4 . OH radicals were examined by PL spectroscopy using TPA as a probe molecule, clearly revealing the OH generation, and moreover, the OH yield and the dye degradation rate show a similar variation between different cases of the catalysis process. This suggested that OH is the dominant reactive species causing the dye degradation. The underlying photo-Fenton mechanism of the composites is discussed.